Carcass composition of organic, broiler (Gallus domesticus) and Malaysian indigenous (Gallus gallusdomesticus) chickens - Mohamad Johar, Ummi Sumilah Soraya; Ganabadi, Shanti; Abdullah, Mohamad Hilmi (2011)
There is an increasing awareness of consumers towards organic food such as organic vegetables or organic chickens. Most of them believe that organic chickens are healthier because of their low amount of fat content. In this study, carcass composition was done to differentiate the carcass of organic, broiler and Malaysian indigenous chickens. Forty adult chickens consisting of 20 broiler chickens, 10 Malaysian indigenous chickens and 10 organic chickens were used in this study. All chickens were slaughtered by cutting the cervical veins and arteries, trachea and oesophagus and then frozen at 0°C for 24 h. The carcasses were then divided into 2 halves; forequarter and hindquarter. Forequarter was separated into breast, wings and ribs whereas the hindquarter was not separated. The muscle, bone, fat and skin of each part were separated, weighed and recorded. Broiler chicken had the highest reading in each part. Malaysian indigenous chicken had the lowest amount of fat and skin compared to broiler and organic chickens. There were no significant differences between organic and Malaysian indigenous chicken.